Scientific and Medical Aspects of Human Reproductive Cloning - National Research Council (The National Academies Press, 2002)
Human reproductive cloning is an assisted reproductive technology that would be carried out with the goal of creating a newborn genetically identical to another human being. It is currently the subject of much debate around the world, involving a variety of ethical, religious, societal, scientific, and medical issues. Scientific and Medical Aspects of Human Reproductive Cloning considers the scientific and medical sides of this issue, plus ethical issues that pertain to human-subjects research. Based on experience with reproductive cloning in animals, the report concludes that human reproductive cloning would be dangerous for the woman, fetus, and newborn, and is likely to fail. The study panel did not address the issue of whether human reproductive cloning, even if it were found to be medically safe, would be—or would not be—acceptable to individuals or society.
Keywords: Biology and Life Sciences; Health and Medicine

Cord Blood: Establishing a National Hematopoietic Stem Cell Bank Program - Institute of Medicine (The National Academies Press, 2005)
With the potential for self-renewal and differentiation, the possibilities for stem cells are enormous. One specific type of stem cell, the hematopoietic progenitor cell (HPC), which is derived from umbilical cord blood (as well as adult bone marrow and mobilized peripheral blood), holds particular promise. To make the most of these HPCs, the Institute of Medicine was asked to consider the optimal structure for a national cord blood program and to address pertinent issues related to maximizing the potential of stem cell technology. Cord Blood: Establishing a National Hematopoietic Stem Cell Bank Program examines: The role of cord blood in stem cell transplantation The current status of blood banks already in existence The optimal structure for the cord blood program The current use and utility of cord blood for stem cell transplants The best way to advance the use of cord blood units and make them available for research Expert advice from leaders in the fields of economics, public health, medicine, and biostatistics combine to make this very timely and topical book useful to a number of stakeholders.
Keywords: Health and Medicine

Assessing the Medical Risks of Human Oocyte Donation for Stem Cell Research: Workshop Report - Institute of Medicine; National Research Council (The National Academies Press, 2007)
It is widely understood that stem cell treatments have the potential to revolutionize medicine. Because of this potential, in 2004 California voters approved Proposition 71 to set up a 10-year, $3 billion program to fund research on stem cells. Under the direction of the California Institute for Regenerative Medicine, this program will pay to build facilities for stem cell research and will fund doctors and scientists to carry out research with the ultimate goal of helping to develop therapies based on stem cells. For this research to move forward, however, will require a steady supply of stem cells, particularly human embryonic stem cells. Those stem cells are collected from developing human embryos created from eggs—or oocytes—harvested from the ovaries of female donors. Thus much of the promise of stem cells depends on women choosing to donate oocytes to the research effort. The oocyte donation process is not without risk, however. Donors are given doses of hormones to trigger the production of more eggs than would normally be produced, and this hormone treatment can have various side effects. Once the eggs have matured in the ovary, they must be retrieved via a surgical procedure that is typically performed under anesthesia, and both the surgery and the anesthesia carry their own risks. Furthermore, given the very personal nature of egg donation, the experience may carry psychological risks for some women as well. With this in mind, in 2006 the California Institute for Regenerative Medicine contracted with the National Academies to organize a workshop that would bring together experts from various areas to speak about the potential risks of oocyte donation and to summarize what is known and what needs to be known about this topic. The Committee on Assessing the Medical Risks of Human Oocyte Donation for Stem Cell Research was formed to plan the workshop, which was held in San Francisco on September 28, 2006. This report is a summary and synthesis of that workshop.
Keywords: Health and Medicine

Stem Cells and the Future of Regenerative Medicine - National Research Council; Institute of Medicine (The National Academies Press, 2002)
Recent scientific breakthroughs, celebrity patient advocates, and conflicting religious beliefs have come together to bring the state of stem cell research—specifically embryonic stem cell research—into the political crosshairs. President Bush’s watershed policy statement allows federal funding for embryonic stem cell research but only on a limited number of stem cell lines. Millions of Americans could be affected by the continuing political debate among policymakers and the public. Stem Cells and the Future of Regenerative Medicine provides a deeper exploration of the biological, ethical, and funding questions prompted by the therapeutic potential of undifferentiated human cells. In terms accessible to lay readers, the book summarizes what we know about adult and embryonic stem cells and discusses how to go about the transition from mouse studies to research that has therapeutic implications for people. Perhaps most important, Stem Cells and the Future of Regenerative Medicine also provides an overview of the moral and ethical problems that arise from the use of embryonic stem cells. This timely book compares the impact of public and private research funding and discusses approaches to appropriate research oversight. Based on the insights of leading scientists, ethicists, and other authorities, the book offers authoritative recommendations regarding the use of existing stem cell lines versus new lines in research, the important role of the federal government in this field of research, and other fundamental issues.
Keywords: Biology and Life Sciences; Health and Medicine

Final Report of the National Academies' Human Embryonic Stem Cell Research Advisory Committee and 2010 Amendments to the National Academies' Guidelines for Human Embryonic Stem Cell Research - Institute of Medicine; National Research Council (The National Academies Press, 2010)
In 2005, the National Academies released the book, Guidelines for Human Embryonic Stem Cell Research, which offered a common set of ethical standards for a field that, due to the absence of comprehensive federal funding, was lacking national standards for research. In order to keep the Guidelines up to date, given the rapid pace of scientific and policy developments in the field of stem cell research, the Human Embryonic Stem Cell Research Advisory Committee was established in 2006 with support from The Ellison Medical Foundation, The Greenwall Foundation, and the Howard Hughes Medical Institute. As it did in 2007 and 2008, the Committee identified issues that warranted revision, and this book addresses those issues in a third and final set of amendments. Specifically, this book sets out an updated version of the National Academies' Guidelines, one that takes into account the new, expanded role of the NIH in overseeing hES cell research. It also identifies those avenues of continuing National Academies' involvement deemed most valuable by the research community and other significant stakeholders.
Keywords: Health and Medicine

2007 Amendments to the National Academies' Guidelines for Human Embryonic Stem Cell Research - Institute of Medicine; National Research Council (The National Academies Press, 2007)
In 2005, the National Academies released the report Guidelines for Human Embryonic Stem Cell Research, which offered a common set of ethical standards for a field that, due to the absence of comprehensive federal funding, was lacking national standards for research. In order to keep the Guidelines up to date, given the rapid pace of scientific developments in the field of stem cell research, the Human Embryonic Stem Cell Research Advisory Committee was established in 2006 with support from The Ellison Medical Foundation, The Greenwall Foundation, and the Howard Hughes Medical Institute. This letter report is the committee's first set of amendments to the Guidelines and clarifies earlier recommendations and conclusions, including the criteria for determining which stem cell lines it is acceptable to use. Future deliberations of the committee will address items for which additional information gathering and more extensive debate and discussion will be necessary.
Keywords: Biology and Life Sciences; Health and Medicine

Guidelines for Human Embryonic Stem Cell Research - Institute of Medicine; National Research Council (The National Academies Press, 2005)
Since 1998, the volume of research being conducted using human embryonic stem (hES) cells has expanded primarily using private funds because of restrictions on the use of federal funds for such research. Given limited federal involvement, privately funded hES cell research has thus far been carried out under a patchwork of existing regulations, many of which were not designed with this research specifically in mind. In addition, hES cell research touches on many ethical, legal, scientific, and policy issues that are of concern to the public. This report provides guidelines for the conduct of hES cell research to address both ethical and scientific concerns. The guidelines are intended to enhance the integrity of privately funded hES cell research by encouraging responsible practices in the conduct of that research.
Keywords: Health and Medicine

2008 Amendments to the National Academies' Guidelines for Human Embryonic Stem Cell Research - Institute of Medicine; National Research Council (The National Academies Press, 2008)
In 2005, the National Academies released the report Guidelines for Human Embryonic Stem Cell Research, which offered a common set of ethical standards for a field that, due to the absence of comprehensive federal funding, was lacking national standards for research. In order to keep the Guidelines up to date, given the rapid pace of scientific developments in the field of stem cell research, the Human Embryonic Stem Cell Research Advisory Committee was established in 2006 with support from The Ellison Medical Foundation, The Greenwall Foundation, and the Howard Hughes Medical Institute. As it did in 2007, the Committee identified issues that warranted revision, and this book addresses those issues in a second set of amendments. Most importantly, this book addresses new scientific developments in reprogramming of somatic cells to pluripotency by adding a new section and revising other relevant sections of the Guidelines.
Keywords: Biology and Life Sciences; Health and Medicine